Evaluation of the time–temperature superposition by comparing neat and glass-fibre-reinforced epoxy using dynamic mechanical thermal analysis - Daniel Esse; Benedikt Scheuring; Frank Henning; Wilfried V. Liebig (Polymer Testing)
Dynamic mechanical thermal analysis is a well-established method to determine the influence of temperature and frequencies on polymers. One challenge inherent to this method is the potential for significant changes in material properties, which can exceed several orders of magnitude and rapidly approach the accuracy or mechanical limits of measurement systems or actuators. In this work, it is shown that a change in the magnitude of the mechanical load within the linear elastic region does not affect the results. Consequently, the test parameters during the DMTA to be adapted to the stiffness of the specimens, allowing materials and volumes closer to the limits of the testing system to be measured. Furthermore, master curves were generated according to the temperature–time superposition for the frequency from the measured sections using a modified method. This was achieved by shifting the loss factor and applying the shift factor to the storage modulus. The tests presented in this work were carried out on continuous fibre-reinforced epoxy resin with a [+45/−45]2s fibre orientation and the neat matrix material itself, up to temperatures above the glass transition area. Wicket plots indicated thereby that the temperature–time superposition is applicable for both material systems. A comparison of the two material systems showed, that the fibre-reinforced specimen is shifted horizontally to a greater extent.